A lacuna protetiva de seguridade social direcionada ao trabalhador de meia-idade - Haik, Cristiane Fátima Grano (2025)
In recent decades, the world has witnessed declining fertility rates and a significant increase in life expectancy, with projections indicating a rise in the percentage of older people within the population in the coming decades. Thus, it is believable that a new perspective should be cast upon “advanced age”, such as protective measures directed at workers between 45 and 64 years old (“middle-aged workers”), to keep them in the labor market at least until they reach retirement age (65 years old for men; 62 years old for women). This is because social security continues to provide pension protection for age only through old-age retirement (“scheduled retirement”), and, in terms of social assistance, from age 65 when it becomes possible to qualify for the continuous cash benefit provided for in the Organic Law on Social Assistance. The thesis aims to propose solutions to fill the protective gap in social security directed at middle-aged workers. To this end, it begins by analyzing the increase in human longevity in recent decades, the origins of the cult of youth and the rejection of aging, as well as international documents dealing with age and ageism. It then addresses the figures related to the aging of the population, specifically of the workforce, and the growing number of people aged 45 or older among Brazilian workers. As a theoretical framework, it draws upon Amartya Sen and Martha Nussbaum's Capabilities Approach, grounded in John Rawls' contractualist theory, which provides a theoretical basis for extending social security protection to middle-aged workers. It is proposed, then, that the risk of “advanced age” can be considered a “social incapacity” caused by ageism. Therefore, protective measures should be extended to middle-aged workers. These measures shouldn’t be limited to the provision of monetary benefits, but configured as professional rehabilitation services, in order to protect these workers from new social demands arising from increased longevity. The research method adopted was hypothetical-deductive, using statistical, observational, and comparative methods